Design of IoT-Based Smart Trash Bin Monitoring Using ESP32 and Firebase - Allya Maulida; Choirunnisa Safa Fayzalmi; Faiz Ata Choirul Anaam; Dikhi Ardiansyah; Muhamad Ariel Gunawan; Nur Ridwan (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Smart Trash Bin Capacity Monitoring System Based on Internet of Things (IoT) is designed to enhance waste management efficiency through automation and connectivity. This system utilizes the ESP32 as the main controller with Wi-Fi communication, and an ultrasonic sensor (HC-SR04) to detect hand presence and measure the trash level. A servo motor is used to automatically open and close the lid. Trash level data is stored in Firebase Realtime Database, and a mobile application developed using Android Studio allows users to monitor the bin status and receive notifications. Additional sensors, such as a gas sensor and weight sensor (HX711 module with load cell), are employed to detect odor and measure the weight of the trash. The system aims to support smarter, more environmentally friendly, and efficient waste management.